Sistem Penentuan Kenaikan Pangkat Prajurit Menggunakan Metode CPI Pada Kodim 0619 Purwakarta - Sevty Nourmantana; Wina Witanti; Asep Id Hadiana (Prosiding SISFOTEK, 2020)
This study designed the application of the system for determining the rank of soldiers using the composite performance index (CPI) method at Kodim 0619 Purwakarta to determine whether or not a soldier passes the various stages of the test, where the values of each of these stages have their own requirements to pass the value of each stage of the test . The test is the same. Samapta is to measure the level of fitness of each soldier. Promotion of soldiers in the Kodim 0619 Purwakarta, namely enlisted and non-commissioned officers. The system for determining the rank of soldiers implements computer-based technology using the Composite Performance Index (CPI) method which was built using the PHP programming language and MySQL DBMS. This system has a function to determine the soldiers who passed or did not pass and determine the ranking of soldiers who passed to get a promotion.